Vaccine Decision-Making in Kaliombo Village: The Role of Halal Awareness, Emergencies, and Religiosity - Arviansyah, Mochamad (Halal Science, 2025)
The controversy surrounding the halal status of the AstraZeneca COVID-19 vaccine, combined with the urgency of pandemic control efforts, has raised concerns among Muslim communities, particularly in rural settings. This study examines the effects of halal awareness, perceived emergency conditions, and religiosity on individuals’ decisions to receive the AstraZeneca vaccine in Kaliombo Village, Bojonegoro Regency. A quantitative survey involving 112 respondents was analyzed using multiple regression, t-tests, F-tests, and Moderated Regression Analysis (MRA). The results show that halal awareness has a statistically significant direct effect on vaccination decisions (t = 2.227, p = 0.028), whereas perceived emergency conditions do not (t = 1.803, p = 0.074). Together, halal awareness and emergency conditions significantly influence vaccination decisions (F = 9.253, p < 0.001), though their explanatory power remains modest (R² = 0.145). Religiosity does not moderate these relationships but functions as an independent predictor (t = 2.653, p = 0.009), increasing the explained variance to 17.5% (R² = 0.175). While statistically significant, these effects are substantively modest, indicating that behavioral decisions are shaped by multiple social and contextual factors. Overall, the findings highlight the prominent role of halal awareness and religiosity in vaccine acceptance and underscore the need to integrate religious considerations into public health communication strategies.